(untitled) (American Journal of Islam and Society, 2005)
The “Muslims and Arabs in Western Politics” conference, held at Indiana University, Bloomington, on September 22-24, 2005 and organized by Abdulkader Sinno (assistant professor, political science and Middle Eastern studies, Indiana University), was highly enriching and intellectually stimulating. The two public lectures and five panels, ranging from civil rights and liberties to public perceptions of Muslims, shed light on various aspects of the complexities of this field and acquainted the participants with cutting-edge research by leading scholars from North America and Western Europe. James Zogby and David Cole delivered the two public lectures on “The Emergent Arab-American Political Constituency” and “Paradigms of Prevention: The Rule of Law and the War on Terror,” respectively. Zogby covered the development of the Arab-American community’s political mobilization and inclusion in mainstream American politics throughout the twentieth century. He narrated his personal experience as a Lebanese immigrant who had experienced the “hard times” of discrimination and exclusion. In addition, he reported on the significant increase in the political mobilization of Muslim minorities in the United States over the last few decades, combined with a growing interest from politicians. His speech ended on a positive note: He is convinced that the community’s trajectory will continue to move forward. On the other hand, David Cole’s talk focused on the state of constitutional law after 9/11. He argued that substantial negative inroads have been made to the five pillars of the rule of law, namely, equality before the law, transparency of procedures, fairness of procedures, checks and balances, and commitment to basic human rights ...